Semilobarholoprosencephaly – A Dreading Congenital Anomaly - Lakhkar, Bhushita B (J Clin Diagn Res, 2017)
Holoprosencephaly (HPE) is a group of structural abnormalities of brain that is an important cause of childhood mortality and morbidity. They usually occur due to impaired midline cleavage of embryonic forebrain i.e., failure of differentiation of the prosencephalon into the telecephalon and diencephalon. De Myer classified this anomaly ranging from alobar to semilobar and lobar type. It can be associated with microcephaly and midline facial anomalies. We present a case of semilobar holoprosencephaly with corpus callosal agenesis.